The Role of Principals in Improving the Professional Competence of Teachers - Nurzaima, Nurzaima; Nursalam, Nursalam; Mawardi, Amirah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Teachers’ professional competence is an important determinant of the quality of education and student achievement. In the Indonesian context, school principals play an important role as instructional leaders, facilitators, and supervisors in strengthening teachers’ professional capacity. This qualitative descriptive study aims to explore the role of school principals in improving the professional competence of teachers at SD Negeri 2 Benua, South Konawe Regency. Data was collected through interviews, observations, and document analysis, involving principals, teachers, and school supervisors. These findings reveal that principals use three key strategies: (1) providing ongoing professional development through workshops and internal training, (2) strengthening collegial collaboration through teacher working groups and peer coaching, and (3) implementing instructional supervision to ensure the quality of teaching. These efforts contribute to a significant improvement in teachers’ mastery of subject matter, pedagogical skills, and classroom management. The study concludes that effective principal leadership practices are essential in promoting sustainable teacher professional competence in primary schools.